An Analysis of Teachers’ Perceptions of Artificial Intelligence Integration in Learning in the Corporate Financial Accounting Department of Vocational High Schools - Endar Dwi Wardana; Sudarmiani Sudarmiani; Ibadullah Malawi (MASI Mandiri Edukasi, 2026)
In the era of digital learning, teachers are required to pioneer innovative education techniques. Teachers are impelled to be competent and capable of utilizing artificial intelligence technology, given the unique challenges educators face in highly structured environments. The objective of this research is to determine teachers' perceptions and willingness to integrate artificial intelligence into the corporate financial accounting department at the vocational high school. The study employed a qualitative descriptive design. Data collection instruments were used to facilitate direct observation, interviews, and documentation. Purposive sampling was applied to select 16 interviewees. The data analysis technique for this study used triangulation, a method comprising several main components. The analytical framework was structured around data collection, data reduction, data presentation, and conclusion drawing. The study aims for three core findings. First, while most educators demonstrate progressive awareness and a positive attitude toward technological adaptation, a digital divide persists, highlighted by a sharp contrast in which some teachers operate at a zero-adoption baseline due to technical anxiety and professional development gaps. Second, AI provides significant advantages by serving as an efficient partner to assist in compiling teaching modules and generating specialized accounting materials. Third, the impacts reveal that AI facilitates personalized learning and time efficiency.